IMPLEMENTASI PROGRAM SULUT MAKMUR BADAN AMIL ZAKAT NASIONAL SULAWESI UTARA DI KOTA MANADO - AMINUDIN, FAZRIANI; RARES, JOYCE; DENGO, SALMIN (Sam Ratulangi University, 2019)
mplementation of the program Sulut Prosperous aims to help underprivileged communities that want to establish or expand a business. But the program is already three years running, has not been able to walk with the maximum. Therefore, this research dimaksudnkan to answer questions about program implementation Agency-affluent Amil Zakat Nasional in Manado in North Sulawesi. In this study researchers use the implementation model of George c. Edward III, the implementation of the policy views of 4 variables that influence the implementation of the policy. Communication is an important factor in the success of a policy, including the orders and decision making. Adequate resources either human resources or financial resources will have an effect on the level of success of the policy. The disposition is the attitude that is owned by implementing such policy ethics and commitment to making this policy work. Bureaucratic structure i.e. how far the range control between the leadership and the subordinates in implementing organizational structure. In this research uses qualitative research methods, descriptive, namely through interviews to 10 informants in direct observation, and search documents that have to do with the program, even in the presence of assisted research guidelines interviews, recording device and stationery to write. The results of the research in General explained that the implementation of the Program in the Prosperous Flammable Amil Zakat Nasional in Manado North Sulawesi has not run optimally.Keyword : Policy Implementation, Sulut Prosperous